Cultivating Entrepreneurial Character Through Market Day Activities at UPT SPF SD Negeri Tamamaung 1 Makassar City - Hasmi, Hasmi; Nurdin, Nurdin; Oktarina, Harti (CV. Rayyan Dwi Bharata, 2025)
The objectives of this research are (1) To determine the implementation of the Project Based Learning model in the independent curriculum in social studies subjects at SMPN Negeri 13 Bontoa Regency. (2) To determine the supporting and inhibiting factors for implementing the Project Based Learning model in the independent curriculum in social studies subjects at SMPN 13 Bontoa, Maros Regency. This research uses a qualitative descriptive research method. Data collection techniques in this research are interviews, observation and documentation. Meanwhile, data analysis is carried out through data collection, data reduction, data presentation, and conclusion drawing/verification. The results of the research show that: 1) The implementation of the project based learning model in the independent curriculum in Social Sciences subjects at SMPN 13 Bontoa, Maros Regency was carried out in accordance with predetermined stages. 2) Supporting factors for the implementation of this project based learning model include the facilities and infrastructure available which are quite complete, the teacher who is very enthusiastic and the closeness of the teacher to the students, and the cost factor that has been provided in the RKAAS.